Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

And the same goes for the existential quantifier: $\exists x \in A : P(x) \; \Leftrightarrow \; \exists x (x \in A \wedge P(x))$. Why couldn’t it be: $\exists x \in A : P(x) \; \Leftrightarrow \; \exists x (x \in A \implies P(x))$ and $\forall x \in A : P(x) \; \Leftrightarrow \; \forall x (x \in A \wedge P(x))$?

share|improve this question
Because we would prefer the statement $\exists x\in A: P(x)$ to actually mean that there is some element $x$ in $A$ that satisfies $P$. If $A$ is empty then your alternative version of it would always be true regardless of $P$. –  Tobias Kildetoft May 21 '13 at 18:58

3 Answers 3

up vote 7 down vote accepted

I thought to coalesce all the answers and comments into one post. A conceivable source is P68 & 69 of How to Prove It by Daniel Velleman as part of the chapter "Equivalences involving Quantifiers."

For the domain of discourse $D$, the formal definitions in green and the inoperative alternatives in Fire Brick Red are:

$\color{green}{\exists \;x \in D \; : P(x) = \exists \;x \in D \; \; ( \;x \in A \wedge P(x) \;) \tag{E = Existential}} $

$ \color{green}{\forall \;x \in D \; : P(x) = \forall \;x \in D \; \; ( \;x \in A \Longrightarrow P(x) \;) \tag{U = Universal}} $

$\color{#B22222}{\exists \; x \in D : P(x) \; = \; \exists \; x \in D \; \; ( \;x \in A \Longrightarrow P(x) \;) \tag{E*}}$

$\color{#B22222}{\forall x \in D : P(x) \; = \; \forall \;x \in D \;\; ( \;x \in A \wedge P(x) \;) \tag{U*}}$

As per Tobias Kildetoft's commentary, (E*) is nonoperational because (E) says that there is an actual element in $x$ which, due to the $\wedge$, must satisfy $P(x)$.
In the extreme case that $A = \emptyset$, $\color{#B22222}{\;x \in A}$ is false so the antecedent of (E*) is a false statement. False statements imply anything, so (E*) doesn't help.

Now, we analyse (U*). $\boxed{\text{Case 1 of 2 : } A \subsetneq D}$
Then there exists at least one point $\in D$ but $\notin A$. Thus $\color{#B22222}{... = \; \forall \;x \in D \;\; ( \;x \in A ... \;)}$ fails.

$\boxed{\text{Case 2 of 2 : } A = D}$
Then the RHS of (U*) becomes: $\; \forall \;x \in D \;\; ( \;x \in \color{#318CE7}{D} \wedge P(x) \;)$ but this just reduces to $\forall \;x \in D \ P(x)$.

Thus, Case 2 is not a problem but Case 1 is. Thus, we circumvent Case 1 with (U).

share|improve this answer
Beautiful use of text color! –  mcb Dec 17 '13 at 2:35

Consider the expression $\forall x \in A : P(x) \; \Leftrightarrow \; \forall x (x \in A \wedge P(x))$. Assuming $A$ to be a proper subset of the domain of discourse, the expression will always be false, because by definition there are $x$ values in the domain of discourse which are not in $A$.

share|improve this answer
What if A equals the domain? –  mcb May 21 '13 at 19:17
@mcb If A equals the domain, then none of this applies. That's why I said a proper subset. If A equals the domain then the expressions will simply be $(\forall x)P(x)$ and $(\exists x)P(x)$. –  Ataraxia May 21 '13 at 19:22

I can't answer your first question. It's just the definition of the notation.

For your second question, by definition of '$\rightarrow$', we have

$\exists x (x\in A \rightarrow P(x)) \leftrightarrow \exists x\neg(x\in A \wedge \neg P(x))$

I think you will agree that this is quite different from

$\exists x (x\in A \wedge P(x))$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.